Implementasi Kebijakan Whistleblowing System di Daerah Otonomi Baru - La Ode Irja Gozali; Rulinawaty Rulinawaty; Usman Pakasi (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to examine the efficiency, effectiveness, adequacy, alignment, responsiveness of employees, and accuracy of the South Papua Provincial Inspectorate in implementing the WBS policy. This type of research is qualitative research. The research instrument is in the form of an interview guide. Data analysis techniques in qualitative research use the N-Vivo software tool. The results of the research show that efficiency in strengthening WBS applications is achieved with high benefits while minimal costs. The inspectorate's adequacy in strengthening WBS applications has not resolved the WBS problem at all. The distribution of regional inspectorates in strengthening the WBS does not meet the element of fairness because there has not been programmed compensation for policy targets, namely WBS users or employees in regional government agencies who make complaints. The responsiveness of employees from government agencies is negative and the accuracy of the WBS program is assessed as having the right objectives. In conclusion, efficiency, effectiveness, adequacy, leveling, employee responsiveness, and accuracy of the South Papua Provincial Inspectorate in implementing the WBS policy have been assessed as having the correct objectives, but there are several indicators which are not fulfill the element of fairness because there has not been programmed compensation for policy targets. Keywords: New Autonomous Region, Policy Implementation, Whistleblowing System.